2017
DOI: 10.1002/brb3.789
|View full text |Cite
|
Sign up to set email alerts
|

Predictive processing increases intelligibility of acoustically distorted speech: Behavioral and neural correlates

Abstract: IntroductionWe examined which brain areas are involved in the comprehension of acoustically distorted speech using an experimental paradigm where the same distorted sentence can be perceived at different levels of intelligibility. This change in intelligibility occurs via a single intervening presentation of the intact version of the sentence, and the effect lasts at least on the order of minutes. Since the acoustic structure of the distorted stimulus is kept fixed and only intelligibility is varied, this allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 69 publications
(143 reference statements)
4
9
0
Order By: Relevance
“…Our third goal was to establish a sensitive metric of measurement of language comprehension which considers the use of context by listeners. We note the caveat in the measurement of language comprehension in above-mentioned studies (e.g., Sheldon et al, 2008;Erb et al, 2013;Hakonen et al, 2017) and extend it further with a metric that we consider is a better measure of language comprehension (Amichetti et al, 2018) in the write-down paradigm (Samar and Metz, 1988).…”
Section: Goals Of This Studymentioning
confidence: 69%
See 1 more Smart Citation
“…Our third goal was to establish a sensitive metric of measurement of language comprehension which considers the use of context by listeners. We note the caveat in the measurement of language comprehension in above-mentioned studies (e.g., Sheldon et al, 2008;Erb et al, 2013;Hakonen et al, 2017) and extend it further with a metric that we consider is a better measure of language comprehension (Amichetti et al, 2018) in the write-down paradigm (Samar and Metz, 1988).…”
Section: Goals Of This Studymentioning
confidence: 69%
“…The measurement of comprehension performance is inconsistent across studies. For instance, Erb et al (2013) and Hakonen et al (2017) measured participants’ performance as proportion of correctly reported words per sentence (“report scores”; Peelle et al, 2013 ). On the other hand, Sheldon et al (2008) asked participants to only report the final word of the sentence and then calculated the proportion of correctly reported words.…”
Section: Introductionmentioning
confidence: 99%
“…For studies with auditory stimulus presentation, we identified all contrasts of sentences against an unintelligible auditory baseline (as in Adank, ): white noise, reversed speech, speech‐envelope noise, tones, signal correlated noise, hummed sentences, low‐pass filtered speech (preserving only an intonational contour, thus unintelligible), and noise vocoded speech. Note that noise‐vocoded speech can be intelligible if coded with more than four channels (Davis, Johnsrude, Hervais‐Adelman, Taylor, & McGettigan, ), or when preceded by intelligible versions of the same sentence (Hakonen et al, ). We therefore, only included contrasts with noise‐vocoded speech as the baseline where it was encoded with four or fewer channels, where it was not preceded by a more intelligible version of the same sentence, and where it was reported to be unintelligible.…”
Section: Methodsmentioning
confidence: 99%
“…From this perspective, object recognition is a matching task. An analogy representing the closest familiar representation in memory is selected by the prefrontal cortex from a matrix of possibilities with differing probabilities (Hakonen et al, 2017). Low probability analogies are suppressed (Depue, 2012).…”
Section: Perceptual Inference-cycles Of Searching the World And Searcmentioning
confidence: 99%
“…The preceding example of prediction error minimization occurs over time with repeated sets of subjective reports followed by sets of eye movements. Presumably this involves cycles of re-entrant processing as information gets passed through thalamo-cortical as well as cortico-cortico loops as the processes of disambiguation, differentiation, sensory integration, and mnemonic integration occur (Edelman and Gally, 2013; Preston and Eichenbaum, 2013; Ohkawa et al, 2015; Richter et al, 2015; Hakonen et al, 2017; Kitamura et al, 2017; Yokose et al, 2017; Chao et al, 2018). The result is an updated memory and model of the world that makes better predictions.…”
Section: Re-entrant Processingmentioning
confidence: 99%